Characterization of Child Influencer's Personal Branding: Analysis of The Father's Role in Shaping Abe's Image on The TikTok Account @Abe_Daily - Ganthira Nur afrian P; Zikri Fachrul Nurhadi; Novie Susanti Suseno (Sinergi International Journal of Communication Sciences, 2026)
This study investigates the growing presence of kid influencers on social media particularly TikTok which signals a shift in how children are represented within the digital landscape. The @abe_daily account, documenting everyday interactions between Abe and his father, is used as the central case. The research aims to identify the personal branding characteristics of the child influencer Abe and to examine the father’s role in constructing this image. Employing a descriptive qualitative design, data were gathered through semi-structured interviews with five informants and two experts in personal branding and child psychology, complemented by social media observation, documentation, and a literature review. Thematic analysis was used to interpret the data. The findings indicate that Abe’s natural disposition, enthusiasm, and spontaneous facial expressions constitute the core elements of his personal branding. The development of this branding corresponds with Montoya’s eight personal branding principles, encapsulated through authenticity, consistency, and emotional resonance. The study concludes that the father’s ethically aware guidance aimed at preventing exploitation while balancing the child’s developmental needs is essential in sustaining Abe’s positive and responsible presence within the digital environment.